The Training Characteristics of World-Class Male Long-Distance Cross-Country Skiers - Torvik, Per-Øyvind; Solli, Guro Strøm; Sandbakk, Øyvind (Frontiers in Sports and Active Living, 2021)
Purpose: To investigate the training characteristics of world-class long-distance cross-country skiers. Methods: Twelve world-class male long-distance cross-country skiing specialists reported training from their best season, through a questionnaire and follow-up interviews. Training data was systemized by training form (endurance, strength, and speed), intensity [low- (LIT), moderate- (MIT), and high-intensity training (HIT)], and exercise mode, followed by a division into different periodization phases. Specific sessions utilized in the various periodization phases were also analysed. Results: The annual training volume was 861±90 h, consisting of 795±88 h (92%) endurance training, 53±17 h (6%) strength training and 13±14 h (2%) speed training. A pyramidal endurance training distribution was employed (i.e. 88.7% LIT, 6.4% MIT and 4.8% HIT). Out of this, 50-60% of the endurance training was performed with double poling (DP), typically in the form of a daily 3-5 h session. A relatively evenly distributed week-to-week periodization of training load was commonly used in the general preparation period, while skiers varied between high-load training weeks and competition weeks with half the training volume and a reduced amount of DP during the competition period. Conclusions: Although the main emphasis in the training of world-class long-distance cross-country skiers is similar to that previously found among Olympic cross-country skiers, some clear differences stand out: long-distance cross-country skiers have longer but fewer training sessions, use a pyramidal intensity distribution pattern, while significantly more of their training time is spent on the DP technique. Accordingly, the training routines seem to match the specific demands of long-distance cross-country skiing.